Cointegration and causality analysis of dynamic linkage between stock market and equity mutual funds in Australia - Sasipa Pojanavatee (Cogent Economics & Finance, 2014)
The existing literature finds conflicting results on the magnitude of price linkages between equity mutual funds and the stock market. The study contends that in an optimal lagged model, the expectations of future prices using knowledge of past price behaviour in a particular equity mutual fund category will improve forecasts of prices of other equity mutual fund categories and the stock market index. The evidence shows that the long-run pricing of equity mutual funds is cointegrated with the stock market index. In the short run, the results indicate that some equity mutual fund categories possess both long-run and short-run exogeneity with the stock market. Therefore, the short-run dynamic indicates short-run Granger causal links running between different equity mutual fund categories.
Keywords: 330; equity mutual fund; cointegration analysis; causality test; vector autoregression (VAR)